Environmental Protection Outlays in Industry and the Return on Assets in the Food Industry in Poland - Maksymilian BĄK; Anna MILEWSKA (Communications of International Proceedings, 2025)
This study examined the impact of changes in fixed asset expenditures for environmental protection, on the return on assets of food enterprises sector and their selected subsectors (meat, bakery, and fruits and vegetables) in Poland from 2011 to 2021. The main reason for this analysis was the relatively limited number of studies addressing the issue of current differences at the subsector level. The study shows the differences at the subsector level and can serve as a starting point for the further research aimed at identifying the causes of the differing responses. The study involves the dynamic panel models. The model estimation was performed using the Generalized Method of Moments (GMM) with the F. Windmeijer correction. The structural parameter estimates were prepared in Gretl, using the Arellano-Bond First Difference Generalized Method of Moments (FDGMM). The research used stratified random sampling which reflects the sectoral structure of medium and large enterprises employing at least 50 employees. The research sample consisted of 193 enterprises representing 15% of the population. It revealed that investment expenditures in water and sewage management significantly impacted the profitability of food enterprises, including those in the meat, bakery, and fruit and vegetable sectors. The increase in expenditures on water and sewage management was associated with the increased profitability in the meat sector and the decreased profitability in the bakery and fruit and vegetable sectors. Additionally, the study demonstrated the varying impact in waste management expenditure value on return on assets in food industry enterprises and their subsectors. The increase in investment expenditures in the waste management was associated with the increase in the return on assets of enterprises in the food industry and the bakery sector.
Keywords: expenditures; environmental protection; return on assets; food enterprises; sectors (meat; bakery; fruits and vegatable) JEL codes: G3; L25; L66.